Development and analysis of lab scaled machine for 3D concrete printing - Mahboob Ali, Muhammad Razif (2021)
Application of 3D concrete printing can contribute to the future enhancement of construction industries. The fundamental objective of the study is to enable users to print concrete into three-dimensional model constructions by modifying and improving the open-source FDM 3D printer. During the development additional testing of a laboratory-scale 3D concrete paste printer that uses a syringe-type extruder was developed. The structure generated by the newly designed 3D concrete paste printer can be analyzed by applying the Taguchi method. Modification and analysis of open-source software for the 3D printer used for printing purposes with concrete paste produces result appropriate ratio of water concrete and corn flour. This is to produce concrete mixture in 3D Print that allowed for the construction of a concrete structure. The development of a prototype 3D printer for concrete structures was fabricated. Various design was analysed to verify their appropriateness and efficacy for the designed 3D Printer. The 3D printer was modified for concrete materials rather than plastic printing, which requires additional time, expense, and creativity on the user's part to do the post-processing. Analysis on 3D printed material was made and it was found that there is significant changes compared to the CAD. This is may be due to the unsuitable mixture and composition. Modification of the 3D printer requires further study on the optimum composition of the material mixture. Normal composition of concrete used in conventional process may not suitable to be used directly for 3D concrete printing due to the nature of the process.